The Influence of Think Pair Share (TPS) Cooperative Learning Model and Initial Ability on Affective Competence Biology Class VIII of SMPN 38 Sijunjung - Rini Silvina (Bioeducation Journal, 2018)
The aim of this research was to reveal the influence of Think Pair Share cooperative learning model and initial ability on affective competence biology class VIII of SMPN 38 Sijunjung. This was a Quasi Experimental research which used 2 x 2 factorial design. The population of the research was the students in class VIII os SMPN 38 Sijunjung in academic year 2015/2016. By using saturated sampling technique, class VIII1 was chosen as the experimental class and class VIII2 was as the control class. Instrument used in this research is observation sheet filled by observer to see student affective competence. The results of the research revealed that Think Pair Share cooperative learning model exerted an influence upon affective competence of the students having either high or low initial ability.